EXTRACTION AND QUANTIFICATION OF SILICON FROM SILICA SAND OBTAINED FROM ZAUMA RIVER, ZAMFARA STATE, NIGERIA - Email, Idrisa Wazamtu; Sani, Nasiru Abdullahi; Abdulsalam, Abba Kura; Abdullahi, Umaru Abubakar (European Scientific Journal, ESJ, 2013)
This is a research on the extraction and quantification of Silicon from Silica Sand obtained from Zauma River in Zamfara state. The Silica Sand sample was removed from the water in Zauma River which was allowed to dry and heated in a heating mantle. Silicon and Silica was extracted from the sample. Quantitative analysis of the sample was then done under the following parameters; determination of loss on ignition, determination of CaO, determination of MgO, determination of Fe2O3, and determination of Al2O3.The results reveals that, the sample contains numerous cations in form of oxides and SiO2 and Si having the highest percentages of 81.5% and 77% respectively. Based on the findings some recommendations were given.